Knowledge About Dental and Oral Hygiene Through Board Game in Adolescents at the Orphanage Yatim Darul Hikmah Surabaya in 2025 - Nurjannah, Najah Akifah; Hadi, Sunomo; Prasetyowati, Silvia (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
An important role is played in oral health in each person, because damage to teeth and gums that is not properly treated can cause pain, interfere with masticatory function, and potentially have an impact on overall body health. One way to maintain dental health is by paying attention to dental hygiene to prevent dental disease. Adolescents are in a period that easily faces oral health problems due to not paying attention to dental and oral hygiene. The problem in this study is the lack of knowledge about dental and oral hygiene in adolescents. The purpose of the study was to determine the knowledge of dental and oral hygiene before and after counseling through board game media for adolescents at the Yatim Darul Hikmah Orphanage Surabaya. This study applied a descriptive research design approach. Information was collected by means of questionnaire sheets given both before and after counseling through board game media. The target or target is 26 adolescents at the Yatim Darul Hikmah Orphanage Surabaya. Data processing applied a questionnaire, and data analysis was carried out by calculating the number of answers from each participant and then converting them into percentages to determine the category of knowledge assessment. The findings from this study indicated that the average knowledge before the board game media was in the poor category (54.2%) and afterward in the good category (84,1%).